2014
DOI: 10.5812/ircmj.18162
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Complications of Coronary Artery Disease

Abstract: Background:Cardiovascular diseases are the leading causes of death around the world. The coronary artery disease (CAD) is one of the most common diseases in this category, which can be the trigger to various psychosocial complications. We believe that inadequate attention has been paid to this issue.Objectives:The purpose of the present study was to explore the psychosocial complications of CAD from the Iranian patients’ perspective.Patients and Methods:A qualitative design based on the content analysis approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…One possible explanation is that the subjective perception of health status differs among patients with different CVDs. Symptoms of IHD usually include occasional pain and possible fear of death [ 47 ], and IHD patients who have a higher nicotine dependence might have a stronger intention to stop smoking in order to prevent the occurrence of a life-threatening health problem. However, strokes are often accompanied with neurologic sequelae, such as paralysis, and therefore stroke patients who have a higher nicotine dependence may develop a stronger desire to smoke despite the stroke-induced disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that the subjective perception of health status differs among patients with different CVDs. Symptoms of IHD usually include occasional pain and possible fear of death [ 47 ], and IHD patients who have a higher nicotine dependence might have a stronger intention to stop smoking in order to prevent the occurrence of a life-threatening health problem. However, strokes are often accompanied with neurologic sequelae, such as paralysis, and therefore stroke patients who have a higher nicotine dependence may develop a stronger desire to smoke despite the stroke-induced disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…15 This creates the potential for a positive feedback loop between CAD and psychosomatic disorders. Aikens et al 16 demonstrated that fear from cardiopulmonary disease was a strong predictor of a composite index of cardiac complaints intensity in those presenting to the ED with NCCP.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of high smoking cessation rate after long-term sick leave is unclear as this is a little researched area. Psychological factors such as fear of death 23) or recurrence 24) might contribute to higher smoking cessation rate compared with those after diagnosis. Our data showing a higher smoking cessation rate among patients with a longer duration of sick leave may support this view, as severity of cancer or CVD might have progressed during long-term sick leave.…”
Section: Discussionmentioning
confidence: 99%